Cryopreservation - Current Advances and Evaluations 2020
DOI: 10.5772/intechopen.89272
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotection of Platelets by Grafted Polymers

Abstract: Unlike red blood cells (RBC) which are stored at 4°C, platelets are stored at 22-24°C (room temperature) due to biophysical and biochemical changes induced by cold temperatures aggregately known as the 'cold storage lesion' (CSL). However, 22°C storage greatly increases the risk of microbial growth, thus limiting the safe storage of platelets to only 5-7 days (versus 42 days for RBC). Consequent to the short shelf life of platelets, blood services face chronic shortages of these life-saving cells. To overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 87 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…According to previous studies, PEGylation can reduce the storage temperature of platelets to 4°C and even sub-zero temperatures without inducing any changes in platelet structure and viability. In addition, PEGylated platelets have also been used to prevent bacteria from reacting with platelets in platelet bags and to increase transfusion safety [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to previous studies, PEGylation can reduce the storage temperature of platelets to 4°C and even sub-zero temperatures without inducing any changes in platelet structure and viability. In addition, PEGylated platelets have also been used to prevent bacteria from reacting with platelets in platelet bags and to increase transfusion safety [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, a methoxy-PEGylation (mPEG) approach was applied by Scott et al . [ 72 ] to reduce the temperature storage and PSL in mPEGylated platelets in an in vitro study. They showed that PEGylation of platelet membranes could reduce the PSLs in platelets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations